I was told it would get easier - Waxman, Abbi (Berkley, 2020)
"Stuck in a bus full of strangers, mother-and-daughter duo Jessica and Emily Burnstein watch their carefully mapped-out college tour devolve into something they never expected in this hilarious and insightful new novel from the author of The Bookish Life of Nina Hill. Jessica and Emily have very different ideas of how this college tour should go. For Emily, it's a last-ditch effort to get excited about her future, because every day in the present feels like such a slog. Can't she just skip straight to the adulting part? It looks so much easier . . . at least on social media. For Jessica, it's a chance to bond with the daughter she seems to have lost. They used to be so close, but then Goldfish crackers and Play-Doh were no longer enough of a draw. She isn't even sure if Emily likes her anymore. To be honest, Jessica isn't entirely sure she likes herself. Together with a dozen strangers-and two familiar enemies-Jessica and Emily travel the East Coast, visiting one prospective college after another, meeting up with family and old friends along the way. Surprises and secrets test their relationship and, in the end, change it forever"--